Concerns in HRM: Probationers’ rights and status in the context of Malaysian employment relations - Muniapan, Balakrishnan; Parasuraman, Balakrishnan; Abdullah, Muhammad Madi; Rathakrishnan, Balan (2008)
This paper analyses the rights and the status of probationers in the context of Malaysian employment relations. A probationer is someone who is on trial to give proof of certain qualifications for a place or status in employment. The term “probation” however, is not found in any of the employment legislation in Malaysia. This means a probationer is an employee in the context of Employment Act 1955 (EA 1955) and a workman in the context of Industrial Relations Act 1955 (IRA 1967). In the employment relations, the probationary period is also an opportunity for both employer and employee to decide whether they are suited for each other. The Industrial Court and the superior courts in Malaysia have over the years ruled that an employee (also refers to workman) on probation enjoys the same rights as a permanent employee. As a result the services of a probationer cannot be terminated without just cause or excuse (Section 20, IRA 1967). Although an employer retains the right to confirm or not to confirm an employee on probation, this prerogative must be exercised in a bona fide manner not arbitrarily or capriciously and there must also be grounds for the decision. In this paper, the authors analyses some of key issues on the rights and status of probationers which also include the employers right to confirm, extend or terminate the services of a probationer. The methodology employed in this paper is the analysis of industrial case laws on probation using criterion based sampling of Industrial Court and superior court awards. Findings from the analysis reveals that many termination awards on probation were made against the employers as the employers have failed or violated the principles of natural justice in the termination of probationers. The basic principle of industrial jurisprudence in Malaysia is that it is the employer who must prove the employee (probationer) guilty, and not the employee (probationer) who must prove himself (herself) not guilty. As such, the burden of prove is on the employer and not on the employee (probationer) for termination cases referred to the Industrial Court. In this paper the authors also provide some recommendation in the management probationers besides other guidelines to improve and create a harmonious employment relationship.